Business Model Canvas Analysis of MSME Beverage SemJoy - Minn, Tong Lie; Nora Pitri Nainggolan (International Journal of Education Management and Religion, 2026)
This study analyzes the business model and sustainability of SemJoy, a micro, small, and medium enterprise (MSME) beverage brand based in Batam, Indonesia, using the Business Model Canvas (BMC) framework. SemJoy offers an innovative drink made from kiamboi (preserved plum), calamansi, and lychee jelly, producing a distinctive combination of sour, sweet, and salty flavors tailored to tropical consumer preferences. Employing a qualitative participatory approach, the research integrates outreach, mentoring, BMC analysis, SWOT analysis, and financial evaluation to map SemJoy’s strategic position and performance. The BMC findings show that SemJoy’s strengths lie in its unique value proposition, affordable and simple production process, use of natural ingredients without preservatives, and localized digital marketing through social media. Key partners include local raw material suppliers and small retailers, while customer segments consist mainly of students, campus communities, and the general public. SWOT analysis indicates strong product differentiation and market opportunities in the growing demand for refreshing beverages, but also highlights challenges such as short shelf life, price volatility of raw materials, and the risk of product imitation. Financial analysis reveals a total sales revenue of IDR 2,480,500 with production costs of IDR 1,412,000, resulting in a net profit of IDR 1,068,500 and a Net Profit Margin (NPM) of 43.08%. The Break-Even Point (BEP) of 29 units demonstrates high economic feasibility. Overall, the study concludes that SemJoy has a viable and competitive business model, and that future sustainability will depend on continuous innovation, improved packaging, supply chain resilience, and strategic partnerships.